Peningkatan Efektivitas Strategi Pemasaran Produk Tabungan dalam Upaya Meningkatkan Jumlah Nasabah pada Perbankan di Wilayah Surabaya - Intan Ayu Purnama; Aliffia Iza Nurheta; Pramudhita Jessika Putri; Sulistyorini Sulistyorini; Ida Ayu Nuh Kartini (Jurnal Pelayanan Masyarakat, 2025)
This community service activity was conducted to assist banking institutions in the Surabaya region in enhancing the effectiveness of marketing strategies for savings products in order to increase the number of customers. The main problems faced by banks include the relatively low level of public interest in saving and the suboptimal implementation of promotional strategies, particularly in the utilization of digital media. This activity employed a collaborative approach through training, mentoring, and joint evaluation with marketing staff of banks in the Surabaya area. This activity commenced with an observation and interview phase to identify the marketing strategies that had been previously implemented. Subsequently, material delivery, technical assistance, along with an evaluation of promotional effectiveness. The results indicate that participants were able to implement more adaptive marketing strategies by utilizing digital media such as social media, website, and banking applications. The implementation of these strategies was shown to increase public interest in opening saving accounts. Furthermore, this activity contributed to enhancing the capacity of marketing staff to design data-driven strategies and to strengthening public financial literacy regarding saving products.